Social media and mental health - Brennan, Cathy; House, Allan (Cambridge University Press, 2023)
In an age when social media is a part of life, there has been much debate about whether it is a force for good or evil. Removing personal opinion from the discussion, this book focusses on research findings to deliver a sorely needed account of the relationship between social media and mental health. Written by experts from a range of disciplines, this book provides a valuable overview of the field. Beginning with research on the nature of social media and their use, the book explores how social media influence mood, body image and general health, and how we can use social media positively. It also explores the link between social media use and specific mental health disorders. Discussion is grounded in the latest research to allow readers to make their own informed judgements. A must-read for professionals in social care, education and mental health, as well as interested general readers.